RESPON TANAMAN SELADA WANGI (Lactuca sativa L. var. Longifolia) SISTEM VERTIKULTUR TERHADAP MEDIA TANAM DAN INTERVAL PENYIRAMAN - Ricky Indri Hapsari; Edyson Indawan; Dewi Ratih Rizki Damayanti; Samuel Chaprianggi Agung (BUANA SAINS, 2022)
This study aimed to determine the response of lettuce plants to type planting media and watering intervals in the verticulture system. This research method used a split-plot design with eight treatments and three replications, including Main plots P1 (2 days watering interval) and P2 (4 days watering interval). The second treatment as sub-plots consisted of planting media: M1 (soil: manure), M2 (manure: sand), M3 (manure: husk charcoal), and M4 (soil: manure: husk charcoal). Observations included growth parameters (plant height, number of leaves, leaf area) and harvest parameters (total fresh weight of plants, fresh weight of roots, total dry weight of plants, dry weight of plants without roots, dry weight of roots). The result of the 2nd watering interval was able to significantly increase the growth component and fragrant lettuce plants compared to the 4th watering interval. Different types of planting media showed a significant effect on plant height but did not affect the number of leaves, leaf area, and components of the yield of fragrant lettuce.